Tissue Engineering in Neuroscience: Applications and Perspectives - Xiaoge Zhang; Fuyao Liu; Zhen Gu (BME Frontiers)
Neurological disorders have always been a threat to human physical and mental health nowadays, which are closely related to the nonregeneration of neurons in the nervous system (NS). The damage to the NS is currently difficult to repair using conventional therapies, such as surgery and medication. Therefore, repairing the damaged NS has always been a vast challenge in the area of neurology. Tissue engineering (TE), which integrates the cell biology and materials science to reconstruct or repair organs and tissues, has widespread applications in bone, periodontal tissue defects, skin repairs, and corneal transplantation. Recently, tremendous advances have been made in TE regarding neuroscience. In this review, we summarize TE’s recent progress in neuroscience, including pathological mechanisms of various neurological disorders, the concepts and classification of TE, and the most recent development of TE in neuroscience. Lastly, we prospect the future directions and unresolved problems of TE in neuroscience.